2014
DOI: 10.3389/fenvs.2014.00036
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of formaldehyde: molecular basis of DNA damage and mutation

Abstract: Formaldehyde is commonly used in the chemical industry and is present in the environment, such as vehicle emissions, some building materials, food, and tobacco smoke. It also occurs as a natural product in most organisms, the sources of which include a number of metabolic processes. It causes various acute and chronic adverse effects in humans if they inhale its fumes. Among the chronic effects on human health, we summarize data on genotoxicity and carcinogenicity in this review, and we particularly focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 51 publications
0
40
0
1
Order By: Relevance
“…Formaldehyde is genotoxic due to its covalent binding to DNA, causing DNA mono-adducts, DNA–DNA cross-links, DPX and DNA glutathione cross-links that can cause mutations and clastogenic effects such as DNA strand breaks, chromosomal aberration (CA), micronucleus (MN) formation and sister chromatid exchange (SCE) as reviewed (IARC 2006; RAC 2012; NRC 2014; Kawanishi et al 2014; Yu et al 2015). Repair of the FA–DNA mono-adducts may include the base excision repair (BER) pathway, and the intra-strand cross-links may be by the nucleotide excision repair (NER) pathway (Kawanishi et al 2014).…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Formaldehyde is genotoxic due to its covalent binding to DNA, causing DNA mono-adducts, DNA–DNA cross-links, DPX and DNA glutathione cross-links that can cause mutations and clastogenic effects such as DNA strand breaks, chromosomal aberration (CA), micronucleus (MN) formation and sister chromatid exchange (SCE) as reviewed (IARC 2006; RAC 2012; NRC 2014; Kawanishi et al 2014; Yu et al 2015). Repair of the FA–DNA mono-adducts may include the base excision repair (BER) pathway, and the intra-strand cross-links may be by the nucleotide excision repair (NER) pathway (Kawanishi et al 2014).…”
Section: Genotoxicitymentioning
confidence: 99%
“…Repair of the FA–DNA mono-adducts may include the base excision repair (BER) pathway, and the intra-strand cross-links may be by the nucleotide excision repair (NER) pathway (Kawanishi et al 2014). FA-induced DPX may be repaired by the NER repair and by the homologous recombination (HR) pathways (de Graaf et al 2009; Kawanishi et al 2014; McHale et al 2014). Furthermore, DPX may partly be broken down by specific proteolytic enzymes, allowing translesion synthesis polymerases (a potentially mutagenic pathway) to replicate across DNA-peptide lesions.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Also, Gomaa et al (2012) studied the genotoxic effects of FA both in rats and workers occupationally exposed to FA and concluded that FA resulted in DNA damage proven by Comet assay in the form of increased tail length and moment in bone marrow of rats and in blood lymphocytes of the workers. Kawanishi et al (2014) studied the molecular basis for possible genotoxicity and carcinogenicity of FA and detected induction of hydroxymethyl mono-adducts on adenine, guanine and cytosine together with methylene crosslinks in DNA.…”
Section: Scientificmentioning
confidence: 99%
“…Formaldehyde can cause inter-and intra-DNA crosslinks, base adducts and DNA-protein crosslinks. It induces N-hydroxymethyl mono-adducts primarily on guanine, adenine and cytosine, and N-methylene crosslinks between adjacent purines in DNA resulting in DNA damage (Kawanishi et al, 2014). Examination of Tp53 mutations from formaldehyde-induced rat nasal squamous cell carcinomas indicated G:C to T:A/C:G transversions, and G:C to A:T transitions (Recio et al, 1992).…”
Section: Dna Adducts and Mutations In Nasal Tumorsmentioning
confidence: 99%